Fourth Five Year Plan Laccadive, Minicoy and Amindivi Islands Administration - Planning Commission (Planning Commission)
The Union Territory of Laccadive, Minicoy and Amindivi Islands consists of twenty islands and three sand banks scattered in the Arabian Sea. Out of these, ten arc inhabited by 24,108 people as per 1961 census. For centuries, these people were completely neglected. Even after Independence it was apparently not possible for the Madras State to go into the detailed needs of these isolated people. It was only after the States Reorganisation and the constitution of these islands into a Union Territory on 1-11-1956 that an integrated approach was made to the development of this area. During the period 1956-58 not much progress could be achieved as investigation and preparation of development schemes tool; some time. It was only in the Third Plan period that substantial progress could be achieved. They arc discussed below.
Laccadive, Minicoy and Amindivi Islands Administration